The Islamic Religiosity And Financial Well-Being: A Moderated Mediation Model Of Financial Behavior And Literacy - Mulyadi Mulyadi; Amelia Oktrivina; Hendryadi Hendryadi; Tyahya Whisnu Hendratni (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: By testing a moderated mediation model, this study aims to examine the mediating role of financial behavior in the relationship between Islamic religiosity, financial behavior, and financial well-being. The study also examines if financial literacy moderates this effect. Methodology/approach: The PROCESS macros version 4.0 was used to assess the hypothesized model based on data from 247 college students. Findings: The findings show that Islamic religiosity influences students' effective financial behavior and well-being. As expected, this study also confirms that financial behavior mediates the effect of Islamic religiosity on financial well-being, and financial literacy mediates this relationship. The role of Islamic religiosity in predicting financial well-being is getting stronger when students have high levels of financial literacy, which has important implications for universities to integrate Islamic values in financial management curricula and courses. Practical implications: The study's implications are directed at financial educators, not only providing financial knowledge to students but also integrating religious values so that they can form positive financial behavior to improve their quality of life in the future. Originality/value: The present study is initial empirical evidence that specifically explores the relationship between Islamic religiosity and financial behavior and its relationship with financial well-being.